2023
DOI: 10.1590/1678-992x-2021-0131
|View full text |Cite
|
Sign up to set email alerts
|

Soybean seeds treated with zinc evaluated by X-ray micro-fluorescence spectroscopy

Abstract: Zinc (Zn) is a micronutrient considered essential to plants which can be supplied through seed treatment. The treatment of soybean [Glycine max (L.) Merr.] seeds with Zn, however, is still not well known as regards the uptake and mobilization dynamics of the nutrient during the germination process. This study aimed to evaluate the uptake and distribution dynamics of Zn applied to soybean seeds at two levels of vigor during germination using X-ray micro-fluorescence spectroscopy (µ-XRF). Zinc treatments corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The absorption of micronutrients applied individually or in combination through seed treatment still raises uncertainty in the scientific community. The results obtained show that regardless of seed vigor, the highest concentration of micronutrients (Cu, Zn and Mn) is found in the hilum and seed coat region, which is in agreement with previous findings for soybean seeds using the µ-XRF technique to analyze zinc absorption [9,34], copper, molybdenum, zinc [8] and nickel [35]. However, these same authors mention that micronutrients applied via seed treatment will later be transferred to the rhizosphere soil and ultimately absorbed by the roots.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The absorption of micronutrients applied individually or in combination through seed treatment still raises uncertainty in the scientific community. The results obtained show that regardless of seed vigor, the highest concentration of micronutrients (Cu, Zn and Mn) is found in the hilum and seed coat region, which is in agreement with previous findings for soybean seeds using the µ-XRF technique to analyze zinc absorption [9,34], copper, molybdenum, zinc [8] and nickel [35]. However, these same authors mention that micronutrients applied via seed treatment will later be transferred to the rhizosphere soil and ultimately absorbed by the roots.…”
Section: Discussionsupporting
confidence: 92%
“…The X-ray fluorescence spectroscopy (XRF) technique stands out in the study of the elemental composition of plant tissues as it allows for in vivo analyses, due to its non-destructive characteristics and minimal sample preparation, in addition to its ability to simultaneously evaluate more than one chemical element in the same sample [7]. The efficiency of the XRF technique has already been confirmed in the evaluation of soybean seed treatment with Cu, Mo and Zn [8], and it has been shown to be a promising technique for the evaluation of soybean seed treatment for improving vigor, being able to clarify the process of the absorption and translocation of micronutrients during the germination process [9].…”
Section: Introductionmentioning
confidence: 98%
“…Because after entering the water-soluble Zn micropyle and hilum, it is distributed from the embryonic axis to the cotyledons, where the rst root exit organized. Since Zn uptake and distribution from cotyledons during seed germination was not associated with seed viability [22], the similarity of this result with control application (26%) showed that ZnO-NPs concentrations were not effective on GVI. According to the GVI results, de ned as the coordinated and sequential sustained activity of the metabolic activity of the plant embryo, ZnO-NPs did not show discernible effects in this process.…”
Section: The Effect Of Zno-npsmentioning
confidence: 60%
“…Hence, to assess whether the effects observed on germination are related to seed Fe-based priming, both benchtop and synchrotron-based micro and nanoprobe X-ray fluorescence spectroscopy (XRF) were employed to assess the Fe localization throughout the cucumber seed tissues. XRF is a powerful analytical tool that has been widely explored in a myriad of seeds, such as maize, , soybeans, ,, kidney beans, , cowpea, , and tomato …”
Section: Results and Discussionmentioning
confidence: 99%